Equinodermos del Parque Nacional Marino Ballena, Pacífico, Costa Rica - Alvarado, Juan José (2005)
Echinoderms from Marino Ballena National Park, Pacific, Costa Rica. A total of 25 species of echinoderms (four asteroids, six ophiuroids, five echinoids and ten holothurians) were recorded at Marino Ballena National Park, using 25 m2 quadrants, parallel to the coast, at seven sites. The ophiuroids were the most abundant group with 581 individuals and the asteroids the less abundant (48 individuals). Echinoderms densities were low, with the exception of the ophiuroids. Diversity, density and the number of groups were higher where sedimentation was lower. We suggest that sedimentation is having a negative effect on the diversity of echinoderms and on the development of the coral reefs in this park. Rev. Biol. Trop. 53(Suppl. 3): 275-284. Epub 2006 Jan 30.